2004
DOI: 10.1159/000074968
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lipid Peroxidation with Antenatal Betamethasone and Oxygen Radical Disorders in Preterm Infants

Abstract: Introduction: Premature infants are highly susceptible to ‘oxygen radical diseases’ (ORD), including bronchopulmonary dysplasia, intraventricular hemorrhage/white matter injury, retinopathy of prematurity, and necrotizing enterocolitis. The incidence of ORD is reduced following antenatal treatment with betamethasone. Oxidant-mediated injury is characterized at the cellular level by peroxidation of lipid membranes. This results in the generation of malondialdehyde (MDA), which can be quantified indirectly by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…Cell membrane oxidation due to ROS results in products of lipid peroxidation such as MDA (18,19). The present study found high levels of MDA in rats with ROP compared to those without ROP, as in previous research (19,20).…”
Section: Discussionsupporting
confidence: 88%
“…Cell membrane oxidation due to ROS results in products of lipid peroxidation such as MDA (18,19). The present study found high levels of MDA in rats with ROP compared to those without ROP, as in previous research (19,20).…”
Section: Discussionsupporting
confidence: 88%
“…0.02) between plasma MDA and urinary MDA 24 h later. Studies have reported higher urinary or plasma MDA levels in preterm infants reflecting higher oxidative stress in this population [7][8][9] . Mocatta et al [10] reported higher serum MDA levels in preterm infants compared to term infants, but this study did not estimate urinary MDA concentrations.…”
Section: Discussionmentioning
confidence: 79%
“…It has been reported that bilirubin can function as a scavenger of reactive oxygen species9. Malondialdehyde (MDA) is a reactive metabolic product that results from the effects of reactive oxygen species on tissues and from a series of reactions that occur during lipid peroxidation10. Plasma MDA levels are a sensitive indicator of lipid peroxidation and thus of oxidative stress1112.…”
mentioning
confidence: 99%